A Prospective Observational Study - Comparing Levonorgestrel Intrauterine System and Other Treatment Modalities for Abnormal Uterine Bleeding in Terms of Bleeding Control, Safety, and Long-Term Outcomes - A, Rathna; Sharma, Nidhi; Christable, Evangeline (Journal of Neonatal Surgery, 2025)
Background: Abnormal uterine bleeding (AUB) affects 10-35% of reproductive-aged women, significantly impacting quality of life. The levonorgestrel-releasing intrauterine system (LNG-IUS) has emerged as a potential first-line treatment, though optimal patient selection criteria remain debated. Methods: In this prospective observational study, 132 women with AUB received LNG-IUS insertion and were followed for 12 months. Primary outcomes included menstrual blood loss (PBAC score) and hemoglobin changes. Secondary outcomes assessed satisfaction (Likert scale), discontinuation rates, and surgical intervention avoidance. Results: Participants demonstrated a 75.7% PBAC score reduction (p<0.001) and 2.2 g/dL hemoglobin increase (p<0.001). Patient satisfaction reached 88.7%, with only 9.6% discontinuation (primarily due to spotting). Hysterectomy was avoided in 85.5% of cases. Subgroup analysis revealed superior outcomes for ovulatory dysfunction (PBAC reduction: 82%) versus adenomyosis (68%). Prolonged spotting (38.7%) was the most common adverse effect, typically resolving by 6 months. Conclusions: LNG-IUS significantly improves AUB symptoms and reduces surgical needs, particularly in ovulatory dysfunction and small fibroids. While adenomyosis patients show slightly diminished response, most achieve meaningful clinical benefit. These findings support LNG-IUS as a first-line AUB therapy, emphasizing the importance of patient selection and anticipatory counseling regarding transient spotting.